(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the use of numeratives in Hindi and Uzbek short stories. It highlights their grammatical and stylistic functions, differences in application, and challenges in translation. Through comparative analysis, the study identifies how these linguistic elements enhance expressiveness and structure in stories.